2021
DOI: 10.1007/s00393-021-01081-5
|View full text |Cite
|
Sign up to set email alerts
|

Work situation of rheumatologists and residents in times of COVID-19

Abstract: Background and objective The work situation is an important dimension of professional life and wellbeing, and a policy lever to strengthen recruitment and retention. This study aims to explore the work situation of physicians and residents in internal medical rheumatology, considering the impact of the coronavirus pandemic COVID-19. Methods A questionnaire-based online survey was conducted in early 2021 at the Hannover Medical School, supported by the Germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(51 reference statements)
2
5
0
Order By: Relevance
“…A survey conducted in early 2021 with support from the German Society of Rheumatology reported similar findings among German rheumatology physicians and residents. 39 These findings are consistent with previous research from other fields of academic medicine demonstrating that women had more difficulties in being taken seriously than men, 40 women were more likely to be excluded from the dominant institutional culture, 41 and that sexism was one of the most common disadvantages to an academic career. 42 Previous research also demonstrated that gender equity interventions could cause resentment among men about perceived positive discrimination of women.…”
Section: Discussionsupporting
confidence: 89%
“…A survey conducted in early 2021 with support from the German Society of Rheumatology reported similar findings among German rheumatology physicians and residents. 39 These findings are consistent with previous research from other fields of academic medicine demonstrating that women had more difficulties in being taken seriously than men, 40 women were more likely to be excluded from the dominant institutional culture, 41 and that sexism was one of the most common disadvantages to an academic career. 42 Previous research also demonstrated that gender equity interventions could cause resentment among men about perceived positive discrimination of women.…”
Section: Discussionsupporting
confidence: 89%
“…These results demonstrated the negative impact of COVID‐19 on rheumatology fellow health and well‐being, with 50% reporting high levels of burnout, 68% with increases in stress, and 25% reporting a negative impact on their physical health 3 . Similar results have been reported in studies from India and Germany as well 53,54 …”
Section: Introductionsupporting
confidence: 81%
“…3 Similar results have been reported in studies from India and Germany as well. 53,54 As we grapple with the process of emerging from the COVID-19 pandemic, it will be critical for training programs to maintain their focus on and prioritize fellow well-being, as the experiences and trauma of the past three years may have a lasting impact. Programs will need to continue to work with their local GME offices and other institutional leaders to ensure adequate support and resources for mental health.…”
Section: Impact On Trainee Well-beingmentioning
confidence: 99%
“…Interviews by Jacobi et al [66] illustrated how success in contraceptives and medicines dispensing by CHW increased access to family planning services across humanitarian–development nexus and led stakeholders view TS necessary during workforce crunch. Likewise, Kuhlmann et al [67] describe how rheumatologist shortage in Germany led care for rheumatoid arthritis and other musculoskeletal disorders shift onto GP and rheumatology specialist assistants. Interestingly, rheumatologists found TS onto rheumatology specialist assistant more useful, compared to delegating onto GP.…”
Section: Discussionmentioning
confidence: 99%